A randomized, open-label, Phase III clinical trial of nivolumab vs. therapy of investigator's choice in recurrent squamous cell carcinoma of the head and neck: A subanalysis of Asian patients versus the global population in checkmate 141. (October 2017) - Kiyota, Naomi; Hasegawa, Yasuhisa; Takahashi, Shunji; Yokota, Tomoya; Yen, Chia-Jui; Iwae, Shigemichi; Shimizu, Yasushi; Hong, Ruey-Long; Goto, Masahiro; Kang, Jin-Hyoung; Sum Kenneth Li, Wing; Ferris, Robert L.; et al.
Highlights: We compared treatments for recurrent SCCHN in Asian patients. Nivolumab was compared with investigator's choice therapy. Median overall survival was 9.5 months with nivolumab and 6.2 with IC. Median progression-free survival was 1.9 and 1.8 months, respectively. Nivolumab provided a survival benefit over IC therapy in this population. Abstract: Objectives: To assess efficacy and safety of nivolumab versus investigator's choice of therapy (IC) in Asian patients with platinum-refractory recurrent or metastatic squamous cell carcinoma of the head and neck (SCCHN). Materials and methods: Thirty-four patients from Japan, Taiwan, Hong Kong, and Korea received nivolumab 3 mg/kg ( n  = 23) every 2 weeks or IC ( n  = 11), as part of a global trial ( n  = 361), until intolerable toxicity or disease progression. The primary endpoint was overall survival (OS). Results: Median OS was 9.5 months (95% confidence interval [CI] 9.1–NR) with nivolumab and 6.2 months (95% CI 2.6–NR) with IC. Seven (30.4%) patients receiving nivolumab and six (54.5%) receiving IC died. The hazard ratio (HR) for risk of death (nivolumab vs. IC) was 0.50 (95% CI 0.17–1.48). Median progression-free survival was 1.9 months (95% CI 1.6–7.5) with nivolumab and 1.8 months (95% CI 0.4–6.1) with IC (HR 0.57 [95% CI 0.25–1.33]). Objective response rates (complete + partial responses) were 26.1% (6/23 patients; 95% CI 10.2–48.4) for nivolumab and 0% (0/11 patients; 95% CI 0.0–28.5) for IC. Sixteen (69.6%) nivolumab-treated patients and 10 (90.9%) patients receiving IC had a treatment-related adverse event, most commonly decreased appetite (21.7%), pruritus, rash, and fatigue (17.4% each) with nivolumab, and nausea, stomatitis, and decreased appetite (27.3% each) with IC. Conclusion: Nivolumab demonstrated a survival advantage compared with conventional treatments in Asian patients with platinum-refractory recurrent or metastatic SCCHN, and was well tolerated. Clinical trial registration NCT02105636.